A case of retroperitoneal abscess: A rare complication of Meckel's diverticulum. (2017) - Hong, Jeana; Park, Sung Bae
Highlights: Meckel' diverticulum is the most common congenital anomaly of the small intestine. It is a relatively not rare disease in the clinical field. But the presentation as a retroperitoneal abscess as complications of Meckel's diverticulum is a very rare clinical entity. In this report, . We present a 31-year-old man with perforated Meckel's divertculum with retroperitoneal abscess. I also reviewed other disease of retroperitoneal abscess. (As I known as, This case report is the first report including review of retroperitoneal abscess). Abstract: Introduction: The frequent complications of Meckel's diverticulum are hemorrhage, intestinal obstruction, and inflammation, and perforation. The presentation as a retroperitoneal abscess as complications of Meckel's diverticulum is a very rare clinical entity. Presentation of case: We report a rare case of perforated Meckel's diverticulum with retroperitoneal abscess. A 31-year-old presented with a half-hour history of severe epigastric pain and diffuse periumbilical pain. Abdominal computed tomography (CT) revealed pneumoperitoneum and retroperitoneal abscesses which air, with diffuse infiltration of the small bowel mesentery and a tubular structure that originated in the ileum at the umbilicus level. Preoperative diagnosis was perforation of Meckel's diverticulum or small bowel perforation. We performed an approximate 10-cm segmental resection of the ileum that contained the Meckel's diverticulum. Discussion: Retroperitoneal abscesses are rare complications of Meckel's diverticulum and are associated with its perforation. Conclusion: The complications of Meckel's diverticulum should be kept in mind in the differential diagnosis of retroperitoneal abscesses.